Catalytic co-pyrolysis of coal and polypropylene plastic into liquid fuel - Sunarno, Sunarno; Reni Yenti, Silvia; Mutamima, Anisa; Huwaidah Husna, Fathiyah; Rahmat Wicakso, Doni; Isnaini, Muhammad Dody (Konversi, 2024)
The decline in fossil fuel sources has stimulated research in the field of renewable fuels. Efforts are currently being made to find alternative energy sources that have high efficiency and are environmentally friendly. By looking at the existing problems, research on the co-pyrolysis of coal and polypropylene (PP) plastic into liquid fuel is interesting to do. The co-pyrolysis process was carried out at 400oC and nitrogen gas was flowed with a flow rate of 100 mL/min for 60 minutes with various ratio of raw material coal/PP plastic (100/0, 75/25, 50/50, 25/75), and ratio of CaO catalyst/raw material (0%, 10%, 15%, 20% w/w). The results showed that with the reduction in the ratio of coal/plastic, the yield of liquid fuel increased. Co-pyrolysis of coal: PP plastic with a ratio of 25:75 with the addition of 20% CaO catalyst obtained 37.56% liquid fuel yield with the characteristics of density of 0.839 g/mL, viscosity of 2.51 cSt, calorific value of 46.813 MJ/kg and pH of 2.9.